(untitled) (Journal of Technology and Operations Management, 2022)
This paper aims to help the SMEs, especially Bumiputera, to analyse their current business performance, generate strategic formulation, consolidate and prioritise the strategic strategy, implementation, and evaluate the implementation to survive in the future and make an adjustment accordingly. The guideline hopes to help the businesses to sustain, stable and grow and can contribute to the Malaysian GDP.